2014
DOI: 10.1111/psyp.12388
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term food deprivation increases amplitudes of heartbeat‐evoked potentials

Abstract: Nutritional state (i.e., fasting or nonfasting) may affect the processing of interoceptive signals, but mechanisms underlying this effect remain unclear. We investigated 16 healthy women on two separate days: when satiated (standardized food intake) and after an 18-h food deprivation period. On both days, heartbeat-evoked potentials (HEPs) and cardiac and autonomic nervous system activation indices (heart rate, normalized low frequency heart rate variability [nLF HRV]) were assessed. The HEP is an EEG pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 86 publications
1
17
3
1
Order By: Relevance
“…The order was counterbalanced across participants. Although findings from earlier studies suggest no main effect of open versus closed eyes on HEPs (19,47), this design was intended to retest this hypothesis in an a priori fashion. Participants were unaware during this phase that the later experimental task would involve their attention-focus on heartbeats.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The order was counterbalanced across participants. Although findings from earlier studies suggest no main effect of open versus closed eyes on HEPs (19,47), this design was intended to retest this hypothesis in an a priori fashion. Participants were unaware during this phase that the later experimental task would involve their attention-focus on heartbeats.…”
Section: Methodsmentioning
confidence: 97%
“…Epochs with nonstereotyped artifacts (e.g., electrode cable movements, swallowing, etc) were excluded from further analysis. As described in previous studies on HEPs (19,22,47,50), eye blink correction was carried out using the Gratton-Coles algorithm (51). EEG analysis was performed with Brain Vision Analyzer 2.0 (Brain Products, Munich, Germany).…”
Section: Electroencephalogram Measurement and Preprocessingmentioning
confidence: 99%
“…As almost all studies in this field are cross-sectional and quasi-experimental in design, it is difficult to come to any conclusions on the direction of this relationship. Beyond clinically relevant eating behavior, the experimental manipulation of eating behavior using short-term food deprivation induces an increase in IA as assessed by heartbeat perception ( Herbert et al, 2012 ) and HEP amplitudes ( Schulz et al, 2015a ). As some neuroendocrinological parameters, such as sympathetic tone or peptide YY output reverse from hyper- to hypo-activation in long-term fasting, one may argue that eating behavior could serve as a coping mechanism to regulate the perception of bodily sensations.…”
Section: Synthesis Of Findings On Interoception and Stressmentioning
confidence: 99%
“…Furthermore, it is possible that variations in HEP amplitude that have been attributed to individual differences in interoceptive sensitivity on the basis of the Schandry counting task are actually due to one or more of the many covariates of interoceptive sensitivity that have been reported. For example, individual differences in attentional focus (Babo‐Rebelo, Wolpert, Adam Hasboun, & Tallon‐Baudry, ; Garcia‐Cordero et al, ; Montoya, Schandry, & Muller, ), emotion/stress/arousal (Couto et al, ; Gray et al, ; Luft & Bhattacharya, ; MacKinnon, Gevirtz, McCraty, & Brown, ), and motivation (Schulz et al, ; Weitkunat & Schandry, ) have all been reported to be associated with HEP amplitude. It seems plausible that any or all of these processes may predispose individuals to acquire more or less accurate, albeit indirect, knowledge of their heart rates and thereby to achieve higher or lower scores on the Schandry HBC test.…”
Section: Introductionmentioning
confidence: 99%